Enantioselective Total Synthesis of (−)‐Limaspermidine and (−)‐Kopsinine by a Nitroaryl Transfer Cascade Strategy. Issue 42 (12th September 2022) - Horst, Brendan; Verdoorn, Daniël S.; Hennig, Sven; van der Heijden, Gydo; Ruijter, Eelco
Abstract: We report an intramolecular conjugate addition/Truce‐Smiles/E1cb cascade of 2‐nitrobenzenesulfonamide‐functionalized cyclohexenones as a new entry to the core scaffold of monoterpene indole alkaloids. The method was applied to the asymmetric total synthesis of (−)‐limaspermidine, (−)‐kopsinilam, and (−)‐kopsinine, as well as the framework of the kopsifoline alkaloids, thus highlighting its complementarity to existing approaches involving the use of indole‐based starting materials or the interrupted Fischer indole synthesis. Furthermore, we show that the cascade tolerates various substituents on the nitroarene, opening the way to other natural products as well as non‐natural analogues. Abstract : 2‐Nitrobenzenesulfonamides can be exploited as functional protective groups by their use in a long‐range nitroarene transfer cascade reaction. Using a suitably functionalized precursor, this process was used as the key step in the enantioselective total synthesis of the monoterpene indole alkaloids (−)‐limaspermidine, (−)‐kopsinilam, and (−)‐kopsinine as well as the unnatural alkaloid (−)‐tetra‐hydrokopsifoline D.